Needs and Preferences in Learning English: Case Study of Informatics Students - Sri Rejeki; Dwi Iswahyuni (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Learning English has become increasingly vital for informatics and information systems students, particularly as it impacts their academic and professional prospects. This study aims to explore the needs and preferences of students in these fields regarding English language instruction, highlighting the importance of tailored educational approaches. The research involves a mixed-methods approach, combining quantitative questionnaires and qualitative interviews with 56 students from Universitas Muhammadiyah Surakarta and Universitas Bina Sarana Informatika. The findings reveal that while students generally feel "confident enough" in their English skills, their actual usage is sporadic, with most using English occasionally or seldom in daily life. Speaking practice is identified as the most beneficial activity for language learning, alongside reading scientific articles and writing. Students prefer interactive and practical learning methods, including regular speaking opportunities, constructive feedback, and collaborative activities. Despite these preferences, students face challenges such as self-confidence, low motivation, ineffective teaching methods, limited vocabulary, pronunciation issues, and grammar and reading comprehension difficulties. The study underscores the need for more engaging and contextually relevant instructional strategies, enhanced learning materials, and technology integration to better support students in mastering English for their specific academic and professional needs.